IMPLEMENTASI MANAJEMEN KEGIATAN EKSTRAKURIKULER DI MAN 1 MURUNG RAYA - Amrullah Amrullah (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2021)
This research was conducted with the aim of knowing about the management function of extracurricular activities in MAN 1 Murung Raya. This research is a qualitative research with a descriptive approach. The subjects of this study were the principal of the madrasah, informan the deputy head of the madrasah for student affairs, the deputy head of the madrasah in the field of curriculum, the supervisor of extracurricular activities, and the teacher. Methods of data collection by interview, observation and documentation. Test the validity of the data by using credibility test, transferability test, dependability test, and confirmability test. The results showed: management of extracurricular activities at MAN 1 Murung Raya includes: first, planning extracurricular activities carried out at the beginning of the school year. What is planned is the teacher, students, facilities and schedule of activities. second, the extracurricular activities are grouped into two, namely compulsory extracurricular and optional extracurricular activities. Extracurricular activities run every day according to a predetermined schedule. third, evaluation of extracurricular activities is carried out once in a while. Things that are evaluated include the targets that have been set, such as the target of winning the madrasah.